Effect of cyhalothrin on Ehrlich tumor growth and macrophage activity in mice - Quinteiro-Filho,W.M. (2009)
Cyhalothrin, a pyrethroid insecticide, induces stress-like symptoms, increases c-fos immunoreactivity in the paraventricular nucleus of the hypothalamus, and decreases innate immune responses in laboratory animals. Macrophages are key elements in cellular immune responses and operate at the tumor-host interface. This study investigated the relationship among cyhalothrin effects on Ehrlich tumor growth, serum corticosterone levels and peritoneal macrophage activity in mice. Three experiments were done with 10 experimental (single gavage administration of 3.0 mg/kg cyhalothrin daily for 7 days) and 10 control (single gavage administration of 1.0 mL/kg vehicle of cyhalothrin preparation daily for 7 days) isogenic BALB/c mice in each experiment. Cyhalothrin i) increased Ehrlich ascitic tumor growth after ip administration of 5.0 x 106 tumor cells, i.e., ascitic fluid volume (control = 1.97 ± 0.39 mL and experimental = 2.71 ± 0.92 mL; P < 0.05), concentration of tumor cells/mL in the ascitic fluid (control = 111.95 ± 16.73 x 106 and experimental = 144.60 ± 33.18 x 106; P < 0.05), and total number of tumor cells in the ascitic fluid (control = 226.91 ± 43.22 x 106 and experimental = 349.40 ± 106.38 x 106; P < 0.05); ii) increased serum corticosterone levels (control = 200.0 ± 48.3 ng/mL and experimental = 420.0 ± 75.5 ng/mL; P < 0.05), and iii) decreased the intensity of macrophage phagocytosis (control = 132.3 ± 19.7 and experimental = 116.2 ± 4.6; P < 0.05) and oxidative burst (control = 173.7 ± 40.8 and experimental= 99.58 ± 41.7; P < 0.05) in vitro in the presence of Staphylococcus aureus. These data provide evidence that cyhalothrin simultaneously alters host resistance to Ehrlich tumor growth, hypothalamic-pituitary-adrenocortical (HPA) axis function, and peritoneal macrophage activity. The results are discussed in terms of data suggesting a link between stress, HPA axis activation and resistance to tumor growth.